Spatial and temporal colocalization of the Golgi apparatus and microtubules rich in detyrosinated tubulin (The Rockefeller University Press, 1990)
The integrity and intracellular distribution of the Golgi apparatus appear to depend upon microtubules. We have found that the microtubules rich in detyrosinated tubulin are located preferentially in the vicinity of the Golgi. Cells were double-stained with antibodies specific for either tyrosinated or detyrosinated tubulin and an antibody to prolactin or wheat germ agglutinin (Golgi markers). Microtubules rich in detyrosinated tubulin showed a close codistribution with the Golgi in three different cultured cell lines GH3, BS-C-1, and AtT20. Disruption of microtubules with nocodazole in GH3 cells resulted in fragmentation and dispersal of the Golgi apparatus as reported previously. During recovery of the microtubules and the Golgi complex after removal of the nocodazole, there was a spatial and temporal colocalization of the Golgi apparatus and microtubules rich in detyrosinated tubulin. Our results suggest that a functional relationship may exist between the structure and organization of the Golgi complex and the detyrosination of alpha- tubulin in microtubules.